Evaluating the Frequency of Postpartum Depression in Marijuana Users With and Without a History of Depression [A226]. (May 2022) - Richards, Ria; Benedict, Jason; Lynch, Courtney; Schaffir, Jonathan
Abstract : INTRODUCTION: Existing literature suggests an association between marijuana use in pregnancy and postpartum depression (PPD). We looked closer at this association by examining the role of depression history. METHODS: Institutional review board approval was attained. We conducted a retrospective cohort study of patients receiving perinatal care at an academic medical center between January 2017 and December 2019. Inclusion criteria included: delivery of a live-born infant at ≥24 weeks, no history of or current opioid dependence, and available Edinburgh Postnatal Depression Scale (EPDS). Marijuana use was self-reported. Screen positive for PPD was defined as scoring 10 or higher on the EPDS. Modified Poisson regression was used to calculate the relative risk (RR) of screening positive for depression. RESULTS: A total of 250 women were included in this analysis. Most were non-Hispanic Black (52%) or White (28%); 61 (24%) reported marijuana use during pregnancy; 102 (41%) had a history of depression and 148 (59%) did not; 39 (16%) screened positive for PPD. With a history of depression, the risk of PPD for those who reported marijuana use was 2.67 times (95% CI, 1.46–4.88) that of those who did not report use. Without a depression history, there was no statistically significant elevation in risk (RR, 1.81; 95% CI, 0.39–8.48). Multivariable analyses are ongoing to assess whether the finding is robust to adjustment for confounding. CONCLUSION: Those with a depression history who report using marijuana during pregnancy may have an increased risk of PPD compared to those who do not report use.